Preferences of Shaykh Muhammad Khal in his commentary - Mahmoud, Asst. Prof. Dr. Mahmoud Abdullah; Bakr, Asst. L. Shawbo Osman (Sulaimani Journal for Humanities, 2023)
This research highlights the most important views of Sheikh Muhammad Al-Khal in his interpretation, across various fields of exegesis. It also addresses the methodology of the Sheikh and the main positive and negative aspects of his interpretation. To achieve this goal, the research relies on a descriptive approach to present Sheikh Al-Khal’s views, followed by an analysis of these views. These issues are covered in two sections and several topics.
Keywords: AlKhal; AlKhals exegesis; views; thought; jurisprudence